2009
DOI: 10.1038/nmat2563
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of the cell dictate stress-induced spreading and differentiation in embryonic stem cells

Abstract: Growing evidence suggests that physical microenvironments and mechanical stresses, besides soluble factors, help direct mesenchymal stem cell fate. However, biological responses to a local force in embryonic stem (ES) cells remain elusive. Here we show that a local cyclic stress via focal adhesions induced spreading in mouse ES (mES) cells but not in mES cell-differentiated (ESD) cells that were 10-fold stiffer. This response was dictated by the cell material property (cell softness), suggesting that a thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
426
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(459 citation statements)
references
References 52 publications
29
426
2
2
Order By: Relevance
“…The expression profile of the enriched flexible SUM149 cell subpopulation shows underexpression of epithelial cytokeratins, actins, and lamins, as well as overexpression of vimentin. These properties could be indicators of greater flexibility and a less differentiated state (5)(6)(7)(8)35), providing support for the proposed mechanism of MS-chip separation.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The expression profile of the enriched flexible SUM149 cell subpopulation shows underexpression of epithelial cytokeratins, actins, and lamins, as well as overexpression of vimentin. These properties could be indicators of greater flexibility and a less differentiated state (5)(6)(7)(8)35), providing support for the proposed mechanism of MS-chip separation.…”
Section: Resultsmentioning
confidence: 77%
“…Applications of these methods to stem cells have revealed the greater deformability of the cytoskeleton and nucleoskeleton in less differentiated cells, whereby deformability generally decreases during differentiation to mature cells (5)(6)(7)(8). Research on cancer cell deformability has also consistently revealed that increased deformability is correlated with increased metastatic potential (9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…As stated above, many cell types are responsive to the mechanical properties of their substrate, including towards their spreading behaviour 14,38 . Thus, as expected, hMSCs cultured on addition-only hydrogel substrates for 1 day spread in a manner that was dependent on the substrate stiffness ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on mESCs revealed that their pluripotency marker Oct3/4 expression is significantly reduced when a local stress is applied to undifferentiated mESCs using magnetic twisting cytometry. 80 Also, the spreading response in mESCs is greater than in airway smooth muscle cells or mESCderived cells. Based on these observations, it can be hypothesized that a threshold cell deformation is crucial for initiating a cell spreading response.…”
Section: Mechanical Stimulation Can Alter Hpsc Fatementioning
confidence: 99%